Thinking Through Translation with Theodoros Angelopoulos: Journeys, Border Crossings, Liminality - Şerban, Adriana (Respectus Philologicus, 2019)
In this paper, I propose to examine the question of journeys, borders, and translation in Theodoros Angelopoulos’ Trilogy of Borders: The Suspended Step of the Stork (1991), Ulysses’ Gaze (1995) and Eternity and a Day (1998), winner of the Palme d’Or at the Cannes Film Festival. It is my aim to contribute, in a small way, to the ongoing discussion about the role of translation in creating understanding, using as a case in point the work of a major contemporary poet of the screen who created his own aesthetics of the journey and whose films are vehicles of discovery, taking the viewer across many borders, on a fabulous – but often unsettling and perilous – voyage which challenges long-held assumptions about self, others, and translation. I suggest there is a plausible link between translation and liminality, a concept introduced in anthropology by Arnold van Gennep in the beginning of the 20th century and later brought to the fore by Victor Turner. I contend that, since in translation there is a tension between the (permanent) source text and the potentially unlimited number of translations, insights from anthropology can shed light on this complex relationship which resembles, in more ways than one, that between liminal experiences and the establishment of permanent structures (which are, usually, born in liminality).